Anti-cracking ceramic glaze water and preparation method thereof

By using raw materials such as sodium feldspar, potassium feldspar, modified kaolin, etc., the problem of poor cracking effect of existing ceramic glaze water is solved, and the high impact and fracture resistance of ceramic glaze water is achieved, which meets the satisfaction of Need for higher crack resistance.

CN119285228AActive Publication Date: 2025-01-10FUJIAN DEHUA COUNTY YONGCHUAN GIFT CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411407431.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-10
Estimated Expiration
2044-10-10

AI Technical Summary

Technical Problem

The existing ceramic glaze water has poor cracking resistance and cannot meet the usage needs of certain scenarios.

Method used

Using raw materials such as sodium feldspar, potassium feldspar, modified kaolin, dolomite, zinc white, barium carbonate, quartz and frit, through specific formulas and preparation methods, anti-crack ceramic glaze with high flexibility and viscosity is prepared. , modified kaolin enhances the bonding force between raw materials through the combination of ethylene-1-octene copolymer and polyethylene, and enhances the bonding performance of glaze water through the grafting reaction of itaconic acid.

Benefits of technology

It significantly improves the impact resistance and tensile resistance of ceramic glaze water, meeting the needs of higher crack resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses anti-cracking ceramic glaze water which comprises albite, potassium feldspar, modified kaolin, dolomite, zinc white, barium carbonate, quartz and frit. The ethylene-1-octylene copolymer has good flexibility, stretchability and tearing strength and high viscosity strength, the binding force between the raw materials is further enhanced through cooperation of the ethylene-1-octylene copolymer and the polyethylene, the impact resistance and the fracture tensile resistance are further enhanced, and meanwhile under the action of the itaconic acid, the mechanical property of the material is improved, so that the mechanical property of the material is improved, and the service life of the material is prolonged. According to the present invention, itaconic acid is adopted as the grafting monomer to react with the ethylene-1-octylene copolymer so as to introduce the itaconic acid group to the ethylene-1-octylene copolymer molecular chain, such that the grafting reaction can enhance the adhesion property, and the anti-cracking strength of the ceramic glaze water can be improved through the setting of the modified kaolin;
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic glazes, and in particular to an anti-cracking ceramic glaze and a preparation method thereof. Background Art

[0002] Glaze is a slurry made by grinding a mixture of multiple raw materials with water in a certain proportion. After being applied to the blank and fired, it can increase the mechanical strength, thermal stability and dielectric strength of the porcelain. It can also beautify the porcelain and make it easier to wipe. However, the ceramic glaze made from ordinary raw materials commonly used in the prior art has poor anti-cracking effect and cannot meet the usage requirements in some scenarios. For this reason, we propose an anti-cracking ceramic glaze and a preparation method thereof. Summary of the invention

[0003] In view of the defects of the prior art, the purpose of the present invention is to provide a crack-resistant ceramic glaze and a preparation method, so as to solve the problem mentioned in the above background technology that the ceramic glaze made from ordinary raw materials in the prior art has poor anti-cracking effect and cannot meet the usage requirements in some scenarios.

[0004] The present invention solves the technical problem by adopting the following technical solution: The present invention provides a crack-proof ceramic glaze, comprising albite, potassium feldspar, modified kaolin, dolomite, zinc white, barium carbonate, quartz, and frit; The specific formula includes the following raw materials (by mass): 16-19 parts of albite, 16-20 parts of potassium feldspar, 15-25 parts of modified kaolin, 5-11 parts of dolomite, 3-7 parts of zinc white, 2-5 parts of barium carbonate, 3-7 parts of quartz and 6-10 parts of frit.

[0005] Preferably, the modified kaolin comprises the following ingredients: kaolin, ethylene-1-octene copolymer, polyethylene, itaconic acid and solvent.

[0006] Preferably, the modified kaolin comprises the following components in percentage by weight: 30-40% kaolin, 12-15% ethylene-1-octene copolymer, 11-13% polyethylene, 3-5% itaconic acid, and the balance ethanol solution.

[0007] Preferably, the preparation method of the modified kaolin comprises the following steps: Step 1: crush the kaolin to 1100-1200 mesh and put it into a ball machine for stirring and heating; Step 2: adding itaconic acid solution to the kaolin heated in step 1, stirring for 3-5 hours, and then washing it with ethanol solution to obtain acidified kaolin; Step 3: Add ethylene-1-octene copolymer and polyethylene to the acidified kaolin, and perform wet ball milling for 6-8 hours in a ball mill using an ethanol solution as a solvent to obtain a mixture; Step 4: Place the mixture at a temperature of 110-120° C., dry it for 7-9 hours, and then calcine it to obtain modified kaolin.

[0008] Preferably, in step 1, the heating temperature is 50-60° C., the heating time is 10-20 min, and the speed of the ball machine is 1300-1500 rpm.

[0009] Preferably, after the mixed material in step 4 is dried, it is calcined at a temperature of 600-700° C. for 2-3 hours to obtain modified kaolin.

[0010] The present invention also provides a method for preparing anti-cracking ceramic glaze, comprising the following steps: S1. Weigh albite, dolomite, potassium feldspar, zinc white and frit according to the proportion, send the above raw materials into a ball mill for impact and grinding, and the ground material is mixture A; S2. Weigh modified kaolin, barium carbonate and quartz according to the ratio, add the above raw materials and mixture A into a mixer to mix until they are uniformly mixed to obtain a uniformly mixed mixture B; S3, transferring the uniformly mixed mixture B to a pool furnace for calcination, and obtaining a mixture C after calcination; S4, crushing the mixture C, rinsing it after crushing, drying it after rinsing, grinding it in a ball mill after drying to obtain a mixture D, and mixing the mixture D with water to make a glaze water; S5. Test the pH value of the glaze water and make appropriate adjustments. Then let the glaze water stand for a while and set it aside.

[0011] Preferably, in step S2, the mixing time is 40-50 min and the rotation speed is 40-60 r / min.

[0012] Preferably, in step S3, the temperature of the pool furnace is 1450-1500° C., and the sintering time is 9-11 hours.

[0013] Preferably, in step S4, after drying, the powder is ground into 170-190 mesh.

[0014] Compared with the prior art, the present invention has the following beneficial effects: The ethylene-1-octene copolymer of the present invention has good flexibility, tensile strength and tear strength, and has high viscosity strength. The ethylene-1-octene copolymer and polyethylene are combined to further enhance the bonding force between the raw materials, thereby helping to enhance the impact resistance and the tensile strength at break resistance. At the same time, under the action of itaconic acid, itaconic acid acts as a grafting monomer and reacts with the ethylene-1-octene copolymer, thereby introducing itaconic acid groups into the molecular chain of the ethylene-1-octene copolymer. This grafting reaction can enhance its bonding performance, thereby improving the anti-cracking strength of ceramic glaze water through the setting of modified kaolin. DETAILED DESCRIPTION

[0015] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0016] The present invention of this embodiment provides a crack-proof ceramic glaze, comprising albite, potassium feldspar, modified kaolin, dolomite, zinc white, barium carbonate, quartz, and frit; The specific formula includes the following raw materials (by mass): 16-19 parts of albite, 16-20 parts of potassium feldspar, 15-25 parts of modified kaolin, 5-11 parts of dolomite, 3-7 parts of zinc white, 2-5 parts of barium carbonate, 3-7 parts of quartz and 6-10 parts of frit.

[0017] The modified kaolin of this embodiment includes the following components: kaolin, ethylene-1-octene copolymer, polyethylene, itaconic acid and solvent.

[0018] The modified kaolin of this embodiment includes the following components in percentage by weight: 30-40% kaolin, 12-15% ethylene-1-octene copolymer, 11-13% polyethylene, 3-5% itaconic acid, and the balance ethanol solution.

[0019] The preparation method of the modified kaolin of this embodiment comprises the following steps: Step 1: crush the kaolin to 1100-1200 mesh and put it into a ball machine for stirring and heating; Step 2: adding itaconic acid solution to the kaolin heated in step 1, stirring for 3-5 hours, and then washing it with ethanol solution to obtain acidified kaolin; Step 3: Add ethylene-1-octene copolymer and polyethylene to the acidified kaolin, and perform wet ball milling for 6-8 hours in a ball mill using an ethanol solution as a solvent to obtain a mixture; Step 4: Place the mixture at a temperature of 110-120° C., dry it for 7-9 hours, and then calcine it to obtain modified kaolin.

[0020] In step 1 of this embodiment, the heating temperature is 50-60° C., the heating time is 10-20 min, and the speed of the ball machine is 1300-1500 rpm.

[0021] In step 4 of this embodiment, after the mixture is dried, it is calcined at a temperature of 600-700° C. for 2-3 hours to obtain modified kaolin.

[0022] A method for preparing a crack-resistant ceramic glaze according to the present embodiment comprises the following steps: S1. Weigh albite, dolomite, potassium feldspar, zinc white and frit according to the proportion, send the above raw materials into a ball mill for impact and grinding, and the ground material is mixture A; S2. Weigh modified kaolin, barium carbonate and quartz according to the ratio, add the above raw materials and mixture A into a mixer to mix until they are uniformly mixed to obtain a uniformly mixed mixture B; S3, transferring the uniformly mixed mixture B to a pool furnace for calcination, and obtaining a mixture C after calcination; S4, crushing the mixture C, rinsing it after crushing, drying it after rinsing, grinding it in a ball mill after drying to obtain a mixture D, and mixing the mixture D with water to make a glaze water; S5. Test the pH value of the glaze water and make appropriate adjustments. Then let the glaze water stand for a while and set it aside.

[0023] In step S2 of this embodiment, the mixing time is 40-50 min and the rotation speed is 40-60 r / min.

[0024] The temperature of the pool furnace of this embodiment is 1450-1500°C, and the sintering time is 9-11h.

[0025] In step S4 of this embodiment, after drying, the powder is ground into 170-190 mesh. Example 1

[0026] The present invention of this embodiment provides a crack-proof ceramic glaze, comprising albite, potassium feldspar, modified kaolin, dolomite, zinc white, barium carbonate, quartz, and frit; The specific formula includes the following raw materials (by mass): 16 parts of albite, 20 parts of potassium feldspar, 15 parts of modified kaolin, 11 parts of dolomite, 3 parts of zinc white, 5 parts of barium carbonate, 3 parts of quartz, and 10 parts of frit.

[0027] The modified kaolin of this embodiment includes the following components: kaolin, ethylene-1-octene copolymer, polyethylene, itaconic acid and solvent.

[0028] The modified kaolin of this embodiment includes the following components in percentage by weight: 40% kaolin, 15% ethylene-1-octene copolymer, 11% polyethylene, 5% itaconic acid, and the balance ethanol solution.

[0029] The preparation method of the modified kaolin of this embodiment comprises the following steps: Step 1: crush the kaolin to 1100 mesh and put it into a ball machine for stirring and heating; Step 2: adding itaconic acid solution to the heated kaolin in step 1, stirring for 3 hours, and then washing it with ethanol solution to obtain acidified kaolin; Step 3: Add ethylene-1-octene copolymer and polyethylene to the acidified kaolin, and perform wet ball milling for 6 hours in a ball mill using an ethanol solution as a solvent to obtain a mixture; Step 4: Place the mixture at a temperature of 110° C., dry it for 7 hours, and then calcine it to obtain modified kaolin.

[0030] In step 1 of this embodiment, the heating temperature is 50° C., the heating time is 10 min, and the speed of the ball machine is 1300 rpm.

[0031] In step 4 of this embodiment, after the mixture is dried, it is calcined at 600° C. for 2 hours to obtain modified kaolin.

[0032] A method for preparing a crack-resistant ceramic glaze according to the present embodiment comprises the following steps: S1. Weigh albite, dolomite, potassium feldspar, zinc white and frit according to the proportion, send the above raw materials into a ball mill for impact and grinding, and the ground material is mixture A; S2. Weigh modified kaolin, barium carbonate and quartz according to the ratio, add the above raw materials and mixture A into a mixer to mix until they are uniformly mixed to obtain a uniformly mixed mixture B; S3, transferring the uniformly mixed mixture B to a pool furnace for calcination, and obtaining a mixture C after calcination; S4, crushing the mixture C, rinsing it after crushing, drying it after rinsing, grinding it in a ball mill after drying to obtain a mixture D, and mixing the mixture D with water to make a glaze water; S5. Test the pH value of the glaze water and make appropriate adjustments. Then let the glaze water stand for a while and set it aside.

[0033] In step S2 of this embodiment, the mixing time is 40 min and the rotation speed is 40 r / min.

[0034] The temperature of the pool furnace in this embodiment is 1450°C and the sintering time is 9 hours.

[0035] In step S4 of this embodiment, after drying, the slurry is ground into 170 mesh. Example 2

[0036] The present invention of this embodiment provides a crack-proof ceramic glaze, comprising albite, potassium feldspar, modified kaolin, dolomite, zinc white, barium carbonate, quartz, and frit; The specific formula includes the following raw materials (by mass): 18 parts of albite, 18 parts of potassium feldspar, 20 parts of modified kaolin, 8 parts of dolomite, 5 parts of zinc white, 4 parts of barium carbonate, 5 parts of quartz, and 8 parts of frit.

[0037] The modified kaolin of this embodiment includes the following components: kaolin, ethylene-1-octene copolymer, polyethylene, itaconic acid and solvent.

[0038] The modified kaolin of this embodiment includes the following components in percentage by weight: 35% kaolin, 13% ethylene-1-octene copolymer, 12% polyethylene, 4% itaconic acid, and the balance ethanol solution.

[0039] The preparation method of the modified kaolin of this embodiment comprises the following steps: Step 1: crush the kaolin to 1150 mesh and put it into a ball machine for stirring and heating; Step 2: adding itaconic acid solution to the heated kaolin in step 1, stirring for 4 hours, and then washing it with ethanol solution to obtain acidified kaolin; Step 3: Add ethylene-1-octene copolymer and polyethylene to the acidified kaolin, and perform wet ball milling in a ball mill using an ethanol solution as a solvent for 7 hours to obtain a mixture; Step 4: Place the mixture at a temperature of 115° C., dry it for 8 hours, and then calcine it to obtain modified kaolin.

[0040] In step 1 of this embodiment, the heating temperature is 55° C., the heating time is 15 min, and the speed of the ball machine is 1400 rpm.

[0041] In step 4 of this embodiment, after the mixture is dried, it is calcined at 650° C. for 2.5 hours to obtain modified kaolin.

[0042] A method for preparing a crack-resistant ceramic glaze according to the present embodiment comprises the following steps: S1. Weigh albite, dolomite, potassium feldspar, zinc white and frit according to the proportion, send the above raw materials into a ball mill for impact and grinding, and the ground material is mixture A; S2. Weigh modified kaolin, barium carbonate and quartz according to the ratio, add the above raw materials and mixture A into a mixer to mix until they are uniformly mixed to obtain a uniformly mixed mixture B; S3, transferring the uniformly mixed mixture B to a pool furnace for calcination, and obtaining a mixture C after calcination; S4, crushing the mixture C, rinsing it after crushing, drying it after rinsing, grinding it in a ball mill after drying to obtain a mixture D, and mixing the mixture D with water to make a glaze water; S5. Test the pH value of the glaze water and make appropriate adjustments. Then let the glaze water stand for a while and set it aside.

[0043] In step S2 of this embodiment, the mixing time is 45 minutes and the rotation speed is 50 r / min.

[0044] The temperature of the pool furnace in this embodiment is 1470°C and the sintering time is 10 hours.

[0045] In step S4 of this embodiment, the powder is ground into 180 meshes after drying. Example 3

[0046] The present invention of this embodiment provides a crack-proof ceramic glaze, comprising albite, potassium feldspar, modified kaolin, dolomite, zinc white, barium carbonate, quartz, and frit; The specific formula includes the following raw materials (by mass): 19 parts of albite, 16 parts of potassium feldspar, 25 parts of modified kaolin, 5 parts of dolomite, 7 parts of zinc white, 2 parts of barium carbonate, 7 parts of quartz, and 6 parts of frit.

[0047] The modified kaolin of this embodiment includes the following components: kaolin, ethylene-1-octene copolymer, polyethylene, itaconic acid and solvent.

[0048] The modified kaolin of this embodiment includes the following components in percentage by weight: 40% kaolin, 12% ethylene-1-octene copolymer, 13% polyethylene, 3% itaconic acid, and the balance ethanol solution.

[0049] The preparation method of the modified kaolin of this embodiment comprises the following steps: Step 1: crush the kaolin to 1200 mesh and put it into a ball machine for stirring and heating; Step 2: adding itaconic acid solution to the kaolin heated in step 1, stirring for 5 hours, and then washing it with ethanol solution to obtain acidified kaolin; Step 3: Add ethylene-1-octene copolymer and polyethylene to the acidified kaolin, and perform wet ball milling in a ball mill using an ethanol solution as a solvent for 8 hours to obtain a mixture; Step 4: Place the mixture at a temperature of 120° C., dry it for 9 hours, and then calcine it to obtain modified kaolin.

[0050] In step 1 of this embodiment, the heating temperature is 60° C., the heating time is 20 min, and the speed of the ball machine is 1500 rpm.

[0051] In step 4 of this embodiment, after the mixture is dried, it is calcined at 700° C. for 3 hours to obtain modified kaolin.

[0052] A method for preparing a crack-resistant ceramic glaze according to the present embodiment comprises the following steps: S1. Weigh albite, dolomite, potassium feldspar, zinc white and frit according to the proportion, send the above raw materials into a ball mill for impact and grinding, and the ground material is mixture A; S2. Weigh modified kaolin, barium carbonate and quartz according to the ratio, add the above raw materials and mixture A into a mixer to mix until they are uniformly mixed to obtain a uniformly mixed mixture B; S3, transferring the uniformly mixed mixture B to a pool furnace for calcination, and obtaining a mixture C after calcination; S4, crushing the mixture C, rinsing it after crushing, drying it after rinsing, grinding it in a ball mill after drying to obtain a mixture D, and mixing the mixture D with water to make a glaze water; S5. Test the pH value of the glaze water and make appropriate adjustments. Then let the glaze water stand for a while and set it aside.

[0053] In step S2 of this embodiment, the mixing time is 50 min and the rotation speed is 60 r / min.

[0054] The temperature of the pool furnace in this embodiment is 1500°C and the sintering time is 11 hours.

[0055] In step S4 of this embodiment, after drying, the slurry is ground into 190 mesh.

[0056] Comparative Example 1. The difference from Example 2 is that the ceramic glaze is made from common raw materials.

[0057] The products of Examples 1-3 and Comparative Example 1 were subjected to performance tests; The ceramic glazes prepared in Examples 1-3 of the present invention and the ceramic glazes prepared using common raw materials were used to manufacture ceramic products for quality inspection. The impact resistance was measured according to ASTM C368 of the United States. Other properties were also tested. The specific results are shown in the following table.

[0058] The innovation of the present invention is: The ethylene-1-octene copolymer of the present invention has good flexibility, tensile strength and tear strength, and has high viscosity strength. The ethylene-1-octene copolymer and polyethylene are combined to further enhance the bonding force between the raw materials, thereby helping to enhance the impact resistance and the tensile strength at break resistance. At the same time, under the action of itaconic acid, itaconic acid acts as a grafting monomer and reacts with the ethylene-1-octene copolymer, thereby introducing itaconic acid groups into the molecular chain of the ethylene-1-octene copolymer. This grafting reaction can enhance its bonding performance, thereby improving the anti-cracking strength of ceramic glaze water through the setting of modified kaolin.

[0059] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0060] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A crack-proof ceramic glaze, characterized in that: Including albite, potassium feldspar, modified kaolin, dolomite, zinc white, barium carbonate, quartz, and frit; The specific formula includes the following raw materials (by mass): 16-19 parts of albite, 16-20 parts of potassium feldspar, 15-25 parts of modified kaolin, 5-11 parts of dolomite, 3-7 parts of zinc white, 2-5 parts of barium carbonate, 3-7 parts of quartz and 6-10 parts of frit.

2. The anti-cracking ceramic glaze according to claim 1, characterized in that: The modified kaolin comprises the following ingredients: kaolin, ethylene-1-octene copolymer, polyethylene, itaconic acid and solvent.

3. The anti-cracking ceramic glaze according to claim 2, characterized in that: The modified kaolin comprises the following components in percentage by weight: 30-40% kaolin, 12-15% ethylene-1-octene copolymer, 11-13% polyethylene, 3-5% itaconic acid, and the balance ethanol solution.

4. The anti-cracking ceramic glaze according to claim 3, characterized in that: The preparation method of the modified kaolin comprises the following steps: Step 1: crush the kaolin to 1100-1200 mesh and put it into a ball machine for stirring and heating; Step 2: adding itaconic acid solution to the kaolin heated in step 1, stirring for 3-5 hours, and then washing it with ethanol solution to obtain acidified kaolin; Step 3: Add ethylene-1-octene copolymer and polyethylene to the acidified kaolin, and perform wet ball milling for 6-8 hours in a ball mill using an ethanol solution as a solvent to obtain a mixture; Step 4: Place the mixture at a temperature of 110-120° C., dry it for 7-9 hours, and then calcine it to obtain modified kaolin.

5. The anti-cracking ceramic glaze according to claim 4, characterized in that: In the step 1, the heating temperature is 50-60° C., the heating time is 10-20 min, and the speed of the ball machine is 1300-1500 rpm.

6. The anti-cracking ceramic glaze according to claim 5, characterized in that: After the mixed material in step 4 is dried, it is calcined at a temperature of 600-700° C. for 2-3 hours to obtain modified kaolin.

7. A method for preparing the anti-cracking ceramic glaze according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Weigh albite, dolomite, potassium feldspar, zinc white and frit according to the proportion, send the above raw materials into a ball mill for impact and grinding, and the ground material is mixture A; S2. Weigh modified kaolin, barium carbonate and quartz according to the ratio, add the above raw materials and mixture A into a mixer to mix until they are uniformly mixed to obtain a uniformly mixed mixture B; S3, transferring the uniformly mixed mixture B to a pool furnace for calcination, and obtaining a mixture C after calcination; S4, crushing the mixture C, rinsing it after crushing, drying it after rinsing, grinding it in a ball mill after drying to obtain a mixture D, and mixing the mixture D with water to make a glaze water; S5. Test the pH value of the glaze water and make appropriate adjustments. Then let the glaze water stand for a while and set it aside.

8. The method for preparing anti-cracking ceramic glaze according to claim 7, characterized in that: In step S2, the mixing time is 40-50 min and the rotation speed is 40-60 r / min.

9. The method for preparing anti-cracking ceramic glaze according to claim 8, characterized in that: In step S3, the temperature of the pool furnace is 1450-1500° C., and the sintering time is 9-11 hours.

10. The method for preparing anti-cracking ceramic glaze according to claim 9, characterized in that: In the step S4, after drying, the powder is ground into 170-190 mesh.

Citation Information

Patent Citations

  • Manufacturing method of antibacterial ceramic glaze

    CN104291866A

  • High-strength whitening glaze slurry for ceramic and preparation method of high-strength whitening glaze slurry

    CN106045322A

  • High-strength porcelain prepared based on waste materials and preparation method thereof

    CN108947480A

  • Easy-to-clean polishing glaze and preparation method thereof

    CN113402169A

  • Glaze for tile

    JP2011246312A